2009
DOI: 10.1111/j.1365-2354.2008.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of fibromyalgia syndrome and quality of life in hospitalized cancer patients

Abstract: To explore the frequency of fibromyalgia syndrome (FMS) among hospitalized cancer patients and address the relationships between pain, fatigue and quality of life with regard to the extent of pain, a cross-sectional and descriptive study was carried out in the Oncology Supportive Care Unit on 122 hospitalized cancer patients. Pain, sleep, disease impact (Fibromyalgia Impact Questionnaire), fatigue (Brief Fatigue Inventory), quality of life (Short Form 36 and European Organization for Research on Treatment of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
7
0
4
Order By: Relevance
“…(2010) showed the existence of multiple active trigger points in neck and shoulder muscles related to greater neck pain intensity in breast cancer survivors. In fact, trigger points are present in different syndromes such as fibromyalgia, which is frequent in cancer survivors (Eyigor et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2010) showed the existence of multiple active trigger points in neck and shoulder muscles related to greater neck pain intensity in breast cancer survivors. In fact, trigger points are present in different syndromes such as fibromyalgia, which is frequent in cancer survivors (Eyigor et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fernández-Lao et al (2010) showed the existence of multiple active trigger points in neck and shoulder muscles related to greater neck pain intensity in breast cancer survivors. In fact, trigger points are present in different syndromes such as fibromyalgia, which is frequent in cancer survivors (Eyigor et al 2009). We suggest that breast cancer may enhance the experience of pain at distant sites presumably via alterations in neuroendocrine profiles or direct sensitising effects on the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…One descriptive study showed that the prevalence of fibromyalgia might be high in hospitalized breast cancer patients [27] . Fibromyalgia symptoms additional to typical cancer symptoms, such as fatigue, might inversely influence the patients' quality of life.…”
Section: Possible Mechanisms Of Exercisementioning
confidence: 99%
“…La depresión representa algo más del 11% del total de variables psicosociales estudiadas, seguida por el estado de ánimo y los aspectos relativos al sueño con algo más del 8%, cada una. En el caso de la depresión se incluye en tres de los cuatro estudios a: mujeres con cáncer de mama (Eyigor et al, 2010), pacientes con bromialgia (Ekici et al, 2008) y sujetos diagnosticados de esquizofrenia (Priebe et al, 2013).…”
Section: Resultsunclassified